Chronic heart failure in younger patients: temporal trends in clinical characteristics, treatment and outcomes over two decades in a nationwide cardiology registry. (25th November 2020) - Iacoviello, M; Marini, M; Gori, M; Gonzini, L; Benvenuto, M; Cassaniti, L; Municino', A; Navazio, A; Ammirati, E; Catalano, M; Floresta, M; Scopelliti, G; et al.
Abstract: Aim of the study: We analyzed the temporal trends in characteristics, therapy and outcomes over two decades of younger chronic heart failure (CHF) patients enrolled in our nationwide registry. Methods: Among the 14823 CHF patients enrolled in the registry since January 1999 through May 2018, 5465 (37%) were aged<65 years (78% men, 54+9 years, left ventricular ejection fraction (LVEF) 36+11%). Patients were divided into 3 cohorts according with the recruitment epoch: 1999–2005; 2006–2011; 2012–2018. We analyzed trends over time of clinical characteristics, therapy, one-year all-cause mortality, all-cause mortality and/or all-cause hospitalization, all-cause mortality and/or CV hospitalization, and all-cause mortality and/or HF hospitalization. Results: From 1999 to 2018 the proportion of patients <65 years declined: 42% in first (2288/5404), 37% in second (1464/3971), 31% in third period (1713/5448). As shown in the Table, the proportion of women, diabetes, ischemic etiology and renin-angiotensin system inhibitor prescription did not change significantly among the three enrollment epochs, whereas preserved LVEF phenotype and prevalence of its driving risk factors increased. The proportion of guideline-recommended drug & device therapies significantly rose over time. All-cause mortality at 1-year follow-up decreased significantly across the 3 epochs studied (Figure). Conclusions: During 20 years, the clinical characteristics, the implementation of recommended treatments and prognosis of patients <65 years enrolled in a nationwide cardiology registry have deeply changed. These modifications reflect the evolution of cardiovascular risk factors and improved management strategies of CV disease. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Fondazione per il Tuo cuore – HCF onlus